Penemuan Hukum oleh Hakim Penetapan Nafkah pasca Perceraian di Pengadilan Agama Pangkajene - Kiljamilawati; Sahratunnisa (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2024)
Legal discovery made by judges in the judicial process can provide a humanist touch in their decisions. judges’ legal findings relating ti divorce cases in the Religious Courts, such as the rights of mut’ah, right of iddah, and rights of past living. The Pangkajene Religious Courts through the decision of the religious Court number 248/Pdt.G/PA.Pkj, based on this decision, the judges tried to make a breakthrough by determining maintenance for the wife such as determining mut’ah maintenance in the amount of 5 grams of gold with the consideration that mut’ah maintenance is a form of apprecitation fot the wife who has struggled and cared for a child who are 3 years old. Apart from that the judge also determined the mut’ah living at 8.000.000 (Eight Million Rupiahs), and the iddah living at 6.000.000 (Six Million Rupiahs) all of which ehwre based on the principle of the husband’s ability.